Confocal fluorescence microscopy: a powerful tool in the study of Chagas' disease - Renato Arruda Mortara; Solange da Silva; Noemi Nosomi Taniwaki (Revista da Sociedade Brasileira de Medicina Tropical, 2000)
Confocal scanning fluorescence microscopy has become widely used in cell biology and pathology. In conjunction with monoclonal antibodies it may turn out to be a powerful diagnostic tool that also enables detailed studies of tissue forms of Trypanosoma cruzi.